2017
DOI: 10.1186/s12864-017-3866-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of DNA methylation in hypothalamus and ovary of Capra hircus

Abstract: BackgroundDNA methylation is a frequently studied epigenetic modification due to its role in regulating gene expression and hence in biological processes and in determining phenotypic plasticity in organisms. Rudimentary DNA methylation patterns for some livestock species are publically available: among these, goat methylome deserves to be further explored.ResultsGenome-wide DNA methylation maps of the hypothalamus and ovary from Saanen goats were generated using Methyl-CpG binding domain protein sequencing (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…These observations are consistent with previous studies on gene methylation status in other livestock species, including goats [ 32 ], horses [ 33 ] and cattle [ 19 ]. Similar patterns were observed in a very recent goat study [ 32 ], in which the distribution of methylated residues was higher in gene bodies than upstream regions in caprine hypothalamus and ovary tissues. In the present study, CpG islands and CGI shores showed a higher CGI and CGI methylation densities than gene bodies and promoter regions, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These observations are consistent with previous studies on gene methylation status in other livestock species, including goats [ 32 ], horses [ 33 ] and cattle [ 19 ]. Similar patterns were observed in a very recent goat study [ 32 ], in which the distribution of methylated residues was higher in gene bodies than upstream regions in caprine hypothalamus and ovary tissues. In the present study, CpG islands and CGI shores showed a higher CGI and CGI methylation densities than gene bodies and promoter regions, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, CpG islands and CGI shores showed a higher CGI and CGI methylation densities than gene bodies and promoter regions, respectively. These data are also consistent with the findings in a study of caprine hypothalamus and ovary tissues, which reported that approximately 50% of the CGIs in are methylated [ 32 ]. Although there were no apparent CG methylation differences between the groups, the overall methylation level (including mCHG and mCHH) of the telogen group was higher than that of the anagen group.…”
Section: Discussionsupporting
confidence: 92%
“…The results revealed that 45 CpG sites were hypomethylated or virtually unmethylated during the SHF cycle. Our findings are supported by previous studies in other livestock species reporting that gene bodies (exons and introns) exhibit the highest levels of CG methylation relative to gene promoters in skin tissue during anagen or telogen (Frattini et al., 2017; Lee et al., 2014).…”
Section: Discussionsupporting
confidence: 91%
“…beads) twice 69 . The methods described below have been reproduced in part from Frattini et al 2017 70 . RNA-Seq libraries were generated using the Illumina TruSeq RNA Sample Preparation v2 Kit but with one-half of the recommended reagent volumes.…”
Section: Resultsmentioning
confidence: 99%